A Biomedical Surface Enhanced Raman Scattering Substrate: Functionalized Three-Dimensional Porous Membrane Decorated with Silver Nanoparticles. (16th December 2015) - Yuan, Li; Fang, Jinghuai; Jin, Yonglong; Wang, Chaonan; Xu, Tian
Abstract : We fabricated a simple, cheap, and functional surface enhanced Raman scattering substrate for biomedical application. Hot spots between two close silver nanoparticles distributed in the skeleton of a three-dimensional porous membrane, especially in the pores, were formed. The dual poles of micropores in the membrane were discussed. The pores could protect the silver nanoparticles in the pores from being oxidized, which makes the membrane effective for a longer period of time. In addition, Staphylococcus aureus cells could be trapped by the micropores and then the Raman signal became stronger, indicating that the functional surface enhanced Raman scattering substrate is reliable.